Porous hematite embedded C and Fe codoped graphitic carbon nitride for electrochemical detection of pineal gland hormone melatonin. (April 2023) - Sebastian, N.; Yu, W.-C.; Balram, D.; Chen, Q.; Shiue, A.; Noman, M.T.; Amor, N.
Abstract: Accurate detection of melatonin, a wide-spectrum antioxidant and vital pineal gland hormone, has high significance. Hence, nanomolar-level electrochemical determination of melatonin using a novel ternary nanocomposite with outstanding electrocatalytic activity is reported in this work. Porous flower-like hematite (α-Fe2 O3 ) nanoparticles were embedded into carbon and iron codoped graphitic carbon nitride (C-Fe-gC3 N4 ) sonochemically to prepare the ternary nanocomposite α-Fe2 O3 /C–Fe-gC3 N4 . A thermal polymerization approach was used for the preparation of C–Fe-gC3 N4, and a hydrothermal method was utilized to synthesize the α-Fe2 O3 nanoparticles. Detailed materials characterization was performed to examine the properties of synthesized materials, and various electrochemical investigations based on cyclic voltammetry and differential pulse voltammetry were conducted to analyze the electrochemical performance of prepared nanocomposite toward melatonin quantification. The melatonin sensor showcased ultra-low detection limit of 4 nM and excellent selectivity, stability, reproducibility, and repeatability. Practical feasibility of melatonin detection in tart cherry, human urine, and melatonin tablets was also validated in this work. Graphical abstract: Image 1 Highlights: Ultrasensitive electrochemical detection of pivotal pineal gland hormone melatonin using novel nanocomposite. Prepared α-Fe2 O3 /C–Fe-gC3 N4 hybrid nanocomposite with excellent electrocatalytic activity. Nanomolar-level detection limit and good sensitivity was achieved for the proposed melatonin sensor. Real sample analysis was conducted in tart cherry, human urine, and melatonin tablet to ensure practicality.